Variation in ‘Bayou Belle’ and ‘Beauregard’ Sweetpotato Root Length in Response to Experimental Phosphorus Deficiency and Compacted Layer Treatments - Villordon, Arthur; Gregorie, Jeffrey Cole; LaBonte, Don; Khan, Awais; Selvaraj, Michael Gomez (American Society for Horticultural Science, 2018)
Phosphorus deprivation (−P) reduced sweetpotato storage root length (SRL) regardless of the presence or absence of a compacted layer (CL). The combination of −P and the presence of a simulated compacted layer (+CL) reduced SRL relative to the P-sufficient (+P) control plants grown without a compacted layer (−CL) by 44% and 40%, respectively, in ‘Bayou Belle’ and ‘Beauregard’ cultivars. In both cultivars, the combination of −P and −CL also reduced SRL by 36% (‘Bayou Belle’) and 28% (‘Beauregard’) relative to the control plants. There was a significant planting date × cultivar effect in the temporal −P studies, with a general trend for SRL reduction with −P at 10-day intervals over a 50-day growing period. −P treatment reduced ‘Bayou Belle’ SRL after 10 days but not after 20 days. In P source plant status studies, the −P/−P treatment (source plant P status/daughter plant P status) was associated with 50% and 48% reduction in SRL in ‘Bayou Belle’ and ‘Beauregard’ daughter plants, respectively, relative to the +P/+P control plants. Taken together, these findings corroborate previous experimental evidence on the role of P in determining root length in other plant species and experimental systems. These experimental findings have practical applications in the management of P in sweetpotato seed and production systems. The results of the current study can lead to follow-up work that validates cultivar-specific P requirements and how such information can be used to optimize P management as it relates to the production of storage roots of consistent length and shape. The methods and approaches used in the current study can be adopted and modified in follow-up investigations that seek to shed light on the precise mechanisms of SRL determination in sweetpotato.